Autoimun yang Menyerang Sistem Maskuloskeletal dan Saraf : Studi Kasus pada Seorang Remaja Perempuan dengan Riwayat Gizi Kurang - Moza Hanu Sabila; Fuja Adinda Sinaga; Yennii Safitri; Nur Izzaty Rahma; Elvi Juliani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
Autoimmune diseases are immune system disorders characterized by an abnormal immune response that attacks the body’s own tissues and may involve multiple organ systems, including the musculoskeletal and nervous systems. This condition can significantly reduce quality of life, particularly in adolescent females who are at higher risk, especially when accompanied by a history of undernutrition. This study aimed to comprehensively examine an autoimmune disease affecting the musculoskeletal and nervous systems in an adolescent female with a history of poor nutritional status. A qualitative case study approach was employed using in-depth interviews. Data were analyzed through thematic analysis to explore the relationship between nutritional status, dietary patterns, supplementation, and clinical manifestations. The findings revealed that a history of undernutrition contributed to the severity of autoimmune symptoms, including bone pain, joint stiffness, gait disturbances, and neurological complaints. This study concludes that nutritional status plays a crucial role in the progression of autoimmune diseases, highlighting the importance of appropriate nutritional interventions, personalized dietary management, and a holistic approach in managing autoimmune conditions in adolescents.